2004
DOI: 10.1038/sj.onc.1207075
|View full text |Cite
|
Sign up to set email alerts
|

Role of TC21/R-Ras2 in enhanced migration of neurofibromin-deficient Schwann cells

Abstract: The neurofibromatosis type 1 tumor suppressor protein neurofibromin, is a GTPase activating protein for H-, N-, K-, R-Ras and TC21/R-Ras2 proteins. We demonstrate that Schwann cells derived from Nf1-null mice have enhanced chemokinetic and chemotactic migration in comparison to wild-type controls. Surprisingly, this migratory phenotype is not inhibited by a farnesyltransferase inhibitor or dominant-negative (dn) (N17)H-Ras (which inhibits H-, N-, and K-Ras activation). We postulated that increased activity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
34
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 58 publications
8
34
0
Order By: Relevance
“…We showed that the PI3-kinase inhibitor, LY294002, attenuates the increased migration of Nf1-/-trigeminal neural crest cells; we have also decreased invasive capacity by treating these cells with the MAP kinase inhibitors PD98059 and U0126 (data not shown). These data are consistent with results using neurofibromindeficient Schwann cells derived from E12.5 dorsal root ganglia (Huang et al, 2004). In order to increase the likelihood that these data will be published, we have added two sets of experiments over the past year: 1) characterization of expression of neural crest markers in the cell populations used (trigeminal neural crest, branchial arch mesenchymal, limb bud mesenchymal), 2) additional inhibitor studies with both the embryonic cell populations and the sarcoma cell lines.…”
Section: Invasiveness Of Nf1-neural Crest Cells (Revised Sow Task 2)supporting
confidence: 82%
“…We showed that the PI3-kinase inhibitor, LY294002, attenuates the increased migration of Nf1-/-trigeminal neural crest cells; we have also decreased invasive capacity by treating these cells with the MAP kinase inhibitors PD98059 and U0126 (data not shown). These data are consistent with results using neurofibromindeficient Schwann cells derived from E12.5 dorsal root ganglia (Huang et al, 2004). In order to increase the likelihood that these data will be published, we have added two sets of experiments over the past year: 1) characterization of expression of neural crest markers in the cell populations used (trigeminal neural crest, branchial arch mesenchymal, limb bud mesenchymal), 2) additional inhibitor studies with both the embryonic cell populations and the sarcoma cell lines.…”
Section: Invasiveness Of Nf1-neural Crest Cells (Revised Sow Task 2)supporting
confidence: 82%
“…2B and 3B). NF1 mediates the inactivation of classic RAS proteins (e.g., KRAS and HRAS) but also nonclassic RAS proteins, including RRAS2 (26). siRNAs targeting KRAS and RRAS2 both caused 4OHT sensitivity, and KRAS silencing also caused moderate ICI182,780 sensitivity (Figs.…”
Section: Resultsmentioning
confidence: 99%
“…PAKs (p21-activated kinases) have also been implicated in SC transformation (Tang et al, 1998). R-Ras and R-Ras2/TC21 may mediate some effects of Nf1 loss in SCs (Huang et al, 2004).…”
Section: Schwann Cell Tumorsmentioning
confidence: 99%